Urinary heavy metal levels and relevant factors among people exposed to e-waste dismantling - Wang, Hongmei; Han, Mei; Yang, Suwen; Chen, Yanqing; Liu, Qian; Ke, Shen (Environment international, 2011)
Primitive electronic waste (e-waste) recycling has become a growing environmental concern, and toxic heavy metals released from e-waste activities may continue to threaten the health of local people. To study the impact of heavy metals in people around e-waste sites, 349 people from e-waste recycling sites (exposure group) and 118 people from a green plantation (control group) were surveyed, and their urinary levels of lead (UPb), cadmium (UCd), manganese (UMn), copper (UCu), and Zinc (UZn) were assayed. Questionnaire surveys for risk factors were also performed and analyzed by using the Pearson correlation analysis. Results indicated that the levels of urinary Cd in both occupational dismantling people {GM(GSD) 0.72(0.71) ug/L} and non-occupational dismantling people {GM(GSD) 0.50(0.79) ug/L} were higher than the control group {GM(GSD) 0.27(0.85) ug/L}. Further analyses of correlations between urinary heavy metal levels and exposure factors in the exposed group revealed positive relationship between the duration of dismantling and the level of UPb (p < 0.05). Meanwhile, rice sources from local village have a positive correlation with the level of UPb and UCd (p < 0.01). Other factors, however, may also have influences on heavy metal burden, and not all urinary heavy metal levels can be contributed to e-waste dismantling exposure levels. Primitive e-waste recycling activities may contribute to the changes of urinary heavy metal levels and increase the health risk for those chronically working on e-waste dismantling.